Recurrent hydatidiform moles: detection of a new mutation in the NLRP7 gene in the family - Balci, Mücahit Furkan; Kaya, Özge Özer; Gezici, Atakan Emre; Oral, Serkan; Akpak, Yaşam Kemal; Karaduman, Arda Batuhan; Cetin, Hamit; Gülhan, İbrahim (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Hydatidiform moles are the most common type of gestational trophoblastic neoplasia. Hyperproliferative vesicular trophoblasts and imperfect fetal development are abnormal pregnancies, and recurrent hydatidiform moles are rare. Mutations in NLRP7 are responsible for recurrent hydatidiform mole. Genetic heterogeneity has been demonstrated in patients with the NLRP7 mutation. This study presents our case with gravida 11, parity 0, histopathologically diagnosed with six hydatidiform moles and five missed abortion histories at age 35. Karyotype analyses of the unrelated couple were normal. A genetic examination revealed a novel mutation of the NLRP7 gene in the patient, his brother, and his parents. Detecting a new NLRP7 mutation in recurrent hydatidiform moles cases provides further evidence for the predetermined role of NLRP7 mutations in the pathophysiology of recurrent moles hydatidiform. Based on our findings, we hope to contribute to the literature by expanding the spectrum of recurrent pregnancy loss associated with NLRP7 mutations in patients.